Topical Rifamycin Prophylaxis in Gynecological and Obstetric Surgery - Ata, Nahit; Kulhan, Mehmet; Kulhan, Nur Gozde; Turkler, Can; Bilgi, Ahmet; Celik, Cetin (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: Antibiotic prophylaxis is one of the most important steps to reduce surgical site infections. First-generation cephalosporin (cefazolin) is used prophylactically in the majority of operations. Rifamycin is a broad-spectrum semisynthetic antibiotic that is bactericidal against gram (+) and gram (˗) microorganisms. To the best of our knowledge, there are no studies on the use of rifamycin in antibiotic prophylaxis. In this study, we aimed to analyze whether there is a difference between the use of only cefazolin and only rifamycin in terms of surgical site infections. STUDY DESIGN: One hundred patients were included in this case-control study during the last quarter period of 2017. These patients (n=100) were divided into two groups according to their antibiotic use; 50 patients who received only 1 g cefazolin constituted Group 1, 50 patients who received only 250 mg topical rifamycin over the incision line based on surgeon’s preference constituted Group 2. RESULTS: The use of prophylactic topical rifamycin reduced the incidence of wound infection. compared with cefazolin. Surgical site infection was detected in 5 (10%) of the patients who received cefazolin, whereas surgical site infection was not observed in patients who received rifamycin (p=0.022). CONCLUSIONS: The use of topical rifamycin is effective but does not imply that systemic antibiotics should replace prophylaxis. The use of rifamycin would aid in systemic antibiotic prophylaxis.